The Effectiveness of A Training Program Based on Flipped Learning Strategy in Achievement in Maths and Achievement Motivation among Seventh Grade Female Students in Jordan - Ibdah, Amal Ali; Al- Shraidh, Mohammad Walid (Journal of Educational and Psychological Sciences, 2020)
The aim of study is to investigate the effectiveness of a training program based Flipped learning strategy in the achievement in Maths and motivation of achievement among the seventh grade students in Jordan. In order to achieve the objectives of this study, a sample of (70) female seventh grade students was selected intentionally in Zahra Al Madaen School in Naor in the year ( 2017/2018). The sample was divided equally into two groups; the control group which was taught by the conventional method consisted of 35 students, the experimental group which was taught by flipped learning method also consisted of 35 students.Two tools were applied on both groups, an achievement test composed of 20 paragraphs, and a questionnaire of achievement motivation developed by Al- Youssafi (2008).In order to test the study hypotheses, the arithmetical means and standard deviations of the students' performance were obtained on the pre and posttest of the achievement test and the achievement motivation questionnaire. ANCOVA was used to find the differences between the average performance.The results showed that there are statistically significant differences between the means of the scores in favour of the Flipped learning strategy. The study recommends the necessity of constructing students' knowledge using the flipped learning strategy in teaching Math’s through employing different activities.
Keywords: Flipped learning; achievement; strategy; motivation